Comprehensive Study of Profiling The Physicochemical Characteristics of Chili Powder From Three Varieties (Red Curly Chili, Red Bird’s Eye Chili, and Ghost Pepper) - Anggraini, Tuty; Yenrina, Rina; Weliardi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This research aimed to examine the physicochemical characteristics of chili powder from three varieties, namely curly chili (Capsicum annuum), bird’s eye chili (Capsicum frutescens), and ghost pepper (Capsicum chinense), which were dried using a food dehydrator at 65 °C for 10 hours. Analyses included physical parameters (length, width, weight, and colour), chemical composition (moisture, ash, fat, protein, and carbohydrate content), and antioxidant activity measured by the DPPH method. The results showed significant differences in morphology and nutritional composition among the varieties. Curly chili exhibited the highest protein content (12.35%) and carbohydrate content (65.68%), while ghost pepper had the highest ash content (6.50%) and fat content (10.17%). In contrast, bird’s eye chili generally fell within the intermediate range for most parameters. The antioxidant activity of all varieties showed high inhibition values (>80%), ranging from 81.33% to 86.46%, although the differences were not statistically significant. Thus, all chili powder varieties met the Indonesian National Standard (SNI) quality requirements and have the potential to be developed as functional food products with longer shelf life. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero hungerSDG 3: Good health and well-beingSDG 8: Decent work and economic growth SDG 12: Responsible consumption and production